Law Enforcement Regarding Witness Protection in the Investigation of Corruption Crimes in Indonesia - Muhamad Naufal Hibatullah; Nabila Genada; Fadhli Ahmad Mujahid; Fely Oktariani (Fakultas Hukum Universitas Bhayangkara Jakarta Raya, 2025)
In the investigation of corruption crimes, the role of witnesses is important, given that witness testimony is the strongest evidence in criminal proceedings. However, often the investigation process involving witness examination does not pay attention to the aspect of witness protection itself. This study applies a normative legal methodology with the main objective of identifying law enforcement regarding witness protection in the investigation of corruption crimes in Indonesia. Specifically, this study analyzes how law enforcement regarding witness protection is carried out in Indonesia. In addition, this study also seeks to examine the coherence of the search for material truth in witness examination in the investigation of corruption crimes in Indonesia. The main findings highlight that there are still obstacles to the enforcement of the law on witness protection, as well as a lack of clarity regarding regulations related to witness protection, especially for witnesses who report corruption crimes. As a solution, it is recommended that mandatory protection regulations be codified immediately to ensure the security of all examination procedures and to reinforce the reliability of evidence in order to achieve substantive justice